The Expression and Functions of Toll-Like Receptors in Atherosclerosis. (24th June 2010) - Cole, Jennifer E.; Georgiou, Ektoras; Monaco, Claudia
Abstract : Inflammation drives atherosclerosis. Both immune and resident vascular cell types are involved in the development of atherosclerotic lesions. The phenotype and function of these cells are key in determining the development of lesions. Toll-like receptors are the most characterised innate immune receptors and are responsible for the recognition of exogenous conserved motifs on pathogens, and, potentially, some endogenous molecules. Both endogenous and exogenous TLR agonists may be present in atherosclerotic plaques. Engagement of toll-like receptors on immune and resident vascular cells can affect atherogenesis as signalling downstream of these receptors can elicit proinflammatory cytokine release, lipid uptake, and foam cell formation and activate cells of the adaptive immune system. In this paper, we will describe the expression of TLRs on immune and resident vascular cells, highlight the TLR ligands that may act through TLRs on these cells, and discuss the consequences of TLR activation in atherosclerosis.